164k views
4 votes
Differentiating Exponential functions In Exercise,find the derivative of the function. See Example 2 and 3.

y = x2ex - 2xex + 2ex

User Oaklodge
by
5.5k points

1 Answer

4 votes

Answer:

Derivative of the expression will be
2e^x

Explanation:

We have given function
y=x^2e^x-2xe^x+2e^x

We have to fond the derivative of the expression

Let
(dy)/(dx)=D_1-D_2+D_3 , here
D_1=x^2e^x,
D_2=2xe^x and
D_3=2e^x

Now first
D_1=x^2(d)/(dx)e^x+e^x(d)/(dx)x^2=x^2e^x+2xe^x


D_2=2[x(d)/(dx)e^x+e^x(d)/(dx)x]=2xe^x+2e^x

Now
D_3=2(d)/(dx)e^x=2e^x

So


D=x^2e^x+2xe^x-(2xe^x+2e^x)+2e^x=2e^x

User Sangeetha Krishna
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.